2018
DOI: 10.22605/rrh4245
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of community participation in an Aboriginal sexual health promotion initiative

Abstract: ABSTRACT:Introduction: Community participation is a collaborative process aimed at achieving community-identified outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…Most of the articles where community need was seen as a priority identified that the research resulted in mutual learning from the researchers, the community and the population group, which in turn was seen as a positive effect in making sustainable changes in either policy or practice. Sherwood and Kendall, 2013 ; Chambers et al , 2018 ; Peake et al , 2020 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the articles where community need was seen as a priority identified that the research resulted in mutual learning from the researchers, the community and the population group, which in turn was seen as a positive effect in making sustainable changes in either policy or practice. Sherwood and Kendall, 2013 ; Chambers et al , 2018 ; Peake et al , 2020 .…”
Section: Discussionmentioning
confidence: 99%
“…The research included in this review had a strong correlation with this criterion—28 articles provided evidence of research benefits to the community. Where research benefit was identified by the researchers for Indigenous communities, there was also evidence of the development of meaningful and ongoing partnerships ( Sherwood and Kendall, 2013 ; Chambers et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Deadly Choices program, now widely used across Australian ACCHOs and includes some SRE in their school-based program, provides a structure that would support further inclusion of SRH champions in these services. 22 Previous studies suggest strong engagement in SRH promotion programs happens when they are designed by and for the community themselves, 39,40 when the workforce includes peers such as family, Elders and community members in delivering support 1,39,41 and uses innovative and creative strategies to engage young people in SRE; 42 however the effectiveness of peer-led education among young First Nations people is currently unknown and further research is needed. 43 How to Support Knowledge Spaces…”
Section: How To Support Knowledge Holdersmentioning
confidence: 99%